2008
DOI: 10.1007/s10616-008-9144-1
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of human hematopoietic stem cells for transplantation: trends and perspectives

Abstract: Umbilical cord blood transplantation is clinically limited by its low progenitor cell content. Ex vivo expansion has become an alternative to increase the cell dose available for transplants. Expansion has been evaluated in several ways such as static cultures combining growth factors or mimicking the natural microenvironment using co-culture systems. However, static cultures have a small volume capacity and therefore large-scale expansion has been addressed using bioreactors. These and other biotechnological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 44 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…The media is the nutritional source for the HSCs and a combination of human/animal serum with a cytokine cocktail [1]. To make allowances for the complexity of the microenvironment for hematopoiesis and the limitations in the knowledge of these complex interactions, serum is added to ensure that the ex vivo conditions mimic the in vivo conditions.…”
Section: Growth Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The media is the nutritional source for the HSCs and a combination of human/animal serum with a cytokine cocktail [1]. To make allowances for the complexity of the microenvironment for hematopoiesis and the limitations in the knowledge of these complex interactions, serum is added to ensure that the ex vivo conditions mimic the in vivo conditions.…”
Section: Growth Mediamentioning
confidence: 99%
“…The serum provides essential nutrients, hormones and growth factors and protects cells from potential damage in the culture environment [3]. However, despite these positive effects, the addition of serum has some disadvantages: unknown composition, which increases the uncontrolled variability of the experiment [2]; possible inhibitory factors [3], which could result in immunological rejection of cells when transplanted [1]. More recently a serum-free media has been used to overcome these disadvantages [2].…”
Section: Growth Mediamentioning
confidence: 99%
“…Results from pilot clinical trials of transplants using expanded UCB-HSC have shown no adverse effects in the patients. However, more clinical trials must be conducted using expanded HSC for guarantying the safety [82]. Very recently, Delaney et al (2010) claimed that when cord blood progenitors expanded ex vivo in the presence of Notch ligand we infused in a clinical setting after a myeloablative preparative regimen for stem cell transplantation, the time to neutrophil recovery was substantially shortened.…”
Section: Ex Vivo Expansion Of Hscmentioning
confidence: 99%
“…Then, because of its availability, ease of gathering and low likelihood of graft versus host diseases, UCB-hematopoietic stem cells (UCB-HSCs) have been broadly applied to treat hematologic disorders, immune deficiency diseases and genetic diseases (Almici et al 1995;Andrade-Zaldívar et al 2008;Kowalczyk et al 2011). Regardless of all advantages mentioned, low count of stem cells per each unit of UCB restricts its application especially for adults (Andrade-Zaldívar et al 2008;Cabrita et al 2003). Consequently, employing methods for ex-vivo expansion of stem cells seems essential (AndradeZaldívar et al 2008;Kowalczyk et al 2011;Broxmeyer et al 2006).…”
Section: Introductionmentioning
confidence: 99%